The effectiveness that language learning strategies have on english intermediate i students' performance on the target language at the FLD at the University of El Salvador - Escobar López, Nelson Bladimir; Mena Osorio, Gabriela Margarita; Glenda Margarita Marroquín Gálvez; Salazar Murcia, Pedro Antonio (San Salvador : Universidad de El Salvador, 2007)
Globalization is currently fading away the barriers people used to find around the world. These old time barriers were languages, commerce and culture. But, nowadays, even the farthest countries and their cultures are exposed worldwide. Besides, these countries get to be known by other peoples, races and cultures easier than ever. Today, languages are not longer a major barrier for countries to communicate with one another. In fact, by using one of the most spoken languages on Earth, English, the world becomes more and more universal for everyone every day. Due to the globalization process the world is involved in, methodological instruction imparted at institutions of superior education is a must for these barriers to be overcome. Colleges and Universities around the world, provide students with every possible tool to master their majors. As a consequence, students become productive and competent. They need all this in order to face the challenges they would encounter when they make their way out into the globalized societies as professionals. Since the University of El Salvador was founded back in 1841, its purpose as a social institution in charge of the superior education in the Republic of El Salvador has been to provide society with competent professionals who contribute to the development of the country. In other words, by means of the systematical instruction given at the University of EL Salvador (UES), graduated students obtain the necessary skills to face the ever changing roles that a professional must have in order to be competitive. More than ever, this is vital for every professional to become part of this new demanding society.
Incluye propuestas de programa académico
Tesis (Licenciatura en Idioma Inglés opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2007
Bibliografía : h. 44-46
Keywords: Inglés -- Enseñanza; Aprendizaje -- Metodología